Association between dietary vitamin E intake and incident cardiovascular disease, cardiovascular, and all-cause mortality: A prospective cohort study using NHANES 2003–2018 data - Qingping Zeng; Mengqian Liao; Yu Li; Fei She; Ping Zhang (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: The relationship between dietary vitamin E intake and the risk of cardiovascular diseases, as well as cardiovascular and all-cause mortality, remains inconclusive. This study aimed to investigate these associations in a large, representative sample of the U.S. population. Methods: We analyzed data from 39,293 participants in the National Health and Nutrition Examination Survey (NHANES) 2003–2018. Dietary vitamin E intake was assessed using 24-h recall data. Outcomes included incident cardiovascular disease (CVD), CVD mortality, and all-cause mortality. We employed weighted logistic and Cox regression models, adjusting for potential confounders. Restricted cubic spline (RCS) analyses and were conducted to assess non-linear relationships. Results: Compared to participants with a vitamin E intake of 4.08 mg or lower (lowest quartile), the multivariable-adjusted odds ratio for those with an intake of 9.86 mg or higher (highest quartile) was 0.57 (95 % CI, 0.50–0.64) for cardiovascular disease (P for trend <0.01). The multivariable-adjusted hazard ratios for participants with a vitamin E intake of 9.86 mg or higher were 0.85 (95 % CI, 0.75–0.98) for all-cause mortality (P for trend = 0.04) and 0.96 (95 % CI, 0.76–1.21) for CVD mortality (P for trend <0.001). RCS analyses revealed non-linear associations for most outcomes, including overall CVD, coronary heart disease, heart attack, stroke, and all-cause mortality (all P-nonlinear <0.05). Conclusions: In this large NHANES cohort, higher dietary intake of vitamin E was associated with reduced risks of cardiovascular disease and all-cause mortality. These findings suggest potential benefits of vitamin E-rich diets in cardiovascular health promotion and mortality reduction.